Loading...

6 - 6 + 6 - 6 + 6 - (6 / 6) = 5

(6/6)+(6/6)+(6/6)+6=9

The answer is 42 minus 36 = 6

(6-6)*6/6 = 6-6

666,660

((6+6)/6)^6 = (12/6)^6 = 2^6 =64

The exponential notation for -6-6-6-6 = -64

6*6, 6*7 and 6*86*6, 6*7 and 6*86*6, 6*7 and 6*86*6, 6*7 and 6*8

6+6+6+6+6+6+6+6+6 =54 This can also be written as 6*9. That is because 6 is added 9 times.

6 plus 6 plus 6 plus 6 plus 6 plus 6 plus 6=6 x 7 =427 x 6 = 426+6+6+6+6+6+6=6 x 7= 42

((6+6)/6)^6 = (12/6)^6 = 2^6 =64

6 +[(6 x 6) / (6 + 6)] = 6 + 36/12 = 6 + 3 = 9

6 + 6 - 6 * 6 - 6 = 6 + 6 - 36 - 6 = -30

6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years 6 years

65

6 + 6 + (6 ÷ 6) = 12 + 1 = 13

You need bracket (parentheses) as well.6*(6 + 6/6) = 6*(6 + 1) = 6*7 = 42You need bracket (parentheses) as well.6*(6 + 6/6) = 6*(6 + 1) = 6*7 = 42You need bracket (parentheses) as well.6*(6 + 6/6) = 6*(6 + 1) = 6*7 = 42You need bracket (parentheses) as well.6*(6 + 6/6) = 6*(6 + 1) = 6*7 = 42

6 + 6 + 6/6 = 13

6-6/6+6*6=36

6*6-6/6 6x6=36-6=30/6=5

(6 x 6) + (6 x 6) - 6 = 66

The additive inverse of 6 is -6, 6 + (-6) = 6 - 6 = 0.The multiplicative inverse of 6 is 1/6, 6 x 1/6 = (6 x 1)/6 = 6/6 = 1

10 time 6 means the value of ' 6 to the power 10 ' . Therefore , it's answer is 6*6*6*6*6*6*6*6*6*6 = 60466176

6 x 6 x 6 x 6 x 6 x 6 = 46656

6 x 6 x 6 x 6 x 6 x 6 x 6 x 6 = 68 = 1679616